2018
DOI: 10.1016/j.anorl.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

International consensus (ICON) on assessment of oropharyngeal dysphagia

Abstract: For the initial objective assessment of OD, it is recommended to perform either a functional endoscopic evaluation of swallowing (FEES) or a videofluoroscopic swallowing study (VFSS). FEES is the more popular investigation given its increased ease of use and accessibility. When evaluating for the presence of aspiration during the objective evaluation of OD, it is recommended to perform either a FEES or a VFSS. In this case, FEES is the favored investigation given its likely increased sensitivity. In order to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
0
34
0
4
Order By: Relevance
“…23 A main weakness of FEES is the overestimation of the quantity of pharynx residue, which can be corrected by complementary videofluoroscopy analysis. 26 We found that bolus consistency affected FEES outcomes in patients with DM1 and in presymptomatic carriers to a similar extent, with more severe impairment when swallowing liquids than when swallowing solids. Specifically, scores for delayed pharyngeal reflex and postswallow residue were similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…23 A main weakness of FEES is the overestimation of the quantity of pharynx residue, which can be corrected by complementary videofluoroscopy analysis. 26 We found that bolus consistency affected FEES outcomes in patients with DM1 and in presymptomatic carriers to a similar extent, with more severe impairment when swallowing liquids than when swallowing solids. Specifically, scores for delayed pharyngeal reflex and postswallow residue were similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 59%
“…Fiberoptic‐endoscopic evaluation is a routine technique to detect the presence and location of postswallow residue, penetration, and aspiration . Furthermore, FEES does not require exposure to radiation, can be repeated as often as required, and allows acquisition of high‐resolution axial endoscopy images . A main weakness of FEES is the overestimation of the quantity of pharynx residue, which can be corrected by complementary videofluoroscopy analysis …”
Section: Discussionmentioning
confidence: 99%
“…This disparity was already found in prior reviews of swallowing assessment in other diseases. 20,31,32,68,69 In addition, previous studies reported poor inter-rater reliability for VFSS, depending on the procedure and bolus consistency used to assess swallowing in adult patients. 70,71 Equally, five reviews in non-NMD adult patients emphasized that consensus on the terminology and study protocols (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Both surgical and non-surgical treatment of HNC can result in transient or permanent OD as described in "Pathophysiology and mechanisms of oropharyngeal dysphagia" section [178]. OD puts the patient not only at risk for aspiration pneumonia, malnutrition, dehydration, and choking, which all increase morbidity but also for reduced QOL [180]. Incidence, diagnosis, and management of malnutrition and dehydration are described in further detail in "Cancer cachexia in head and neck cancer" and "Treatment of cancer cachexia" sections.…”
Section: Complications Due To Oropharyngeal Dysphagia In Head and Necmentioning
confidence: 99%